Pollution by metals and toxicity assessment using Caenorhabditis elegans in sediments from the Magdalena River, Colombia. (May 2016) - Tejeda-Benitez, Lesly; Flegal, Russell; Odigie, Kingsley; Olivero-Verbel, Jesus
Abstract: The Magdalena River is the most important river in Colombia, supplying over 70% of the population of fish and drinking water, and it also is the main river transportation way of the country. It receives effluents from multiple sources along its course such as contaminant agricultural and industrial discharges. To evaluate the toxicity profile of Magdalena River sediments through endpoints such as survival, locomotion, and growth, wild type strains of Caenorhabditis elegans were exposed to aqueous extracts of the sediments. To identify changes in gene expression, GFP transgenic strains were used as reporter genes. Physiological and biochemical data were correlated with metal concentration in the sediments, identifying patterns of toxicity along the course of the river. Levels of some metals such as Cd, Cu, and Ni were above TEC and PEC limits. Effects in survival, growth, and locomotion were observed in most of the samples, and changes in gene expression were evident in the genes mtl-2, sod-4, and gst-1 using fluorescence expression. Cadmium and lead were the metals which were primarily associated with sediment toxicity, and the sampling sites with the highest increased expression of stress response genes were Barrancabermeja and Girardot. However, the diverse nature of toxic profiles observed in C. elegans in the study area showed the pervasiveness of different types of discharges throughout the river system. Graphical abstract: Highlights: The Magdalena River has high levels of some metals such as Cd, Cu, and Ni. Most sediment extracts affected lethality, growth, and locomotion of C. elegans. Sediment extracts induced expression changes in mtl-2, sod-4, and gst-1. Sediment toxicity was primarily associated with Cd and Pb. Highest toxicity was observed for samples collected in mining and industrial areas. Abstract : In Magdalena River sediments, Cd and Pb were associated with toxicity in Caenorhabditis elegans and expression of stress response genes were related to mining and industrial areas.